U.S. Global Defense Posture, 1783-2011 - Pettyjohn, Stacie L. (RAND Corporation, 2012)
This monograph describes the evolution of the U.S. global defense posture from 1783 to the present as the nation grew from a relatively weak and insular regional power into the preeminent global power. As new and unpredictable threats emerge, alliance relationships are revised, and resources decline, past efforts at dealing with similar problems yield important lessons for future decisions.